Sequence and function-based screening of goat rumen metagenome for novel lipases - Mukendi, Mujinga Grace (Vaal University of Technology, 2019)
Lipases have been one of the important biocatalysts that catalyse the transformation of lipids to yield very important products that can be of beneficial in food, agriculture, pharmaceutical medicine and for the biodiesel production. In the search for novel biocatalysts, notably lipases, the conventional culture-based techniques were used but it can only address sourcing the biomolecule from 1-10% of the microbial population leaving the wealth of the biomolecules packed in 90-99% of the microbial community unaccounted for. Metagenomic technique, which is culture-independent, was developed as a comprehensive approach to address literally 100% of the microbial population thereby maximizing the chances of obtaining novel biocatalysts with superior physico-chemical and catalytic traits. In principle, any biomolecule including lipase could be sourced from any biologically-active environment, of which animal rumen is one. However, among the rumenant animals goat has diverse feeding habit, thereby laying ground for increased microbial diversity in its gastro-intestinal tract. It was thus, postulated that goat rumen could be potential source of novel lipase isoforms. Therefore, the aim of the study was to extract metagenomic DNA from goat rumen and construct a metagenomic fosmid library and screen the library for lipase isoforms. The fosmid clones were functionally screened using 1% tributyrin as a substrate and five positive clones were selected. From the five clones, two fosmids were selected for further study. Following nucleotide sequencing and in-silico analysis of the insert of the two selected clones, one lipase encoding open reading frame (Lip-VUT3 and Lip-VUT5) from each fosmid clones of approximately 212 and 248 amino acids, respectively, was identified. The amino acid sequences of the Lip-VUT3 ORF contained a classical conserved lipase GSDL sequence motif while the amino acid sequences of the Lip-VUT5 ORF contained a classical G-L-S-L-G conserved lipase/esterase motif sequence. The two genes (Lip-VUT3 and Lip-VUT5) were successfully expressed in Escherichia coli BL21 (DE3) and the purified enzymes exhibited respective temperature optima of 60 °C and 70 °C, and respective pH optima of 6.0 and 10.0. Further biochemical characterisation indicated that Lip-VUT3 and Lip-VUT5 lipases showed tolerance towards a wide concentration (50%-100%) of methanol. Lip-VUT3 had a Km value of 0.287 mM while Lip-VUT5 had a Km value of 0.556 Mm. This shows that Lip-VUT3 lipase has a higher affinity for olive oil than Lip-VUT5. Lip-VUT3 and Lip-VUT5 were characterised to be true lipases that have been recovered from the rumen environment through metagenomic approach. Therefore, the study proved that metagenomic approach helps in recovering novel lipase isoforms with potential down stream industrial and therapeautic applications from goat rumen metagenome, a rich but untapped source.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Functional metagenomic; Goat rumen; Lipase; Dissertations, Academic -- South Africa.; Lipase -- Biotechnology.